Analisis Ontologi Pendidikan Islam dalam Membangun Konsep Hakikat Manusia sebagai Khalifah di Era Kontemporer - Fatkhul Azis; Mujiburrohman (Lembaga Yasin AlSys, 2026)
The crisis of human identity in the modern era is characterized by the growing influence of materialism, individualism, moral relativism, and the fragmentation of knowledge, which have shifted the orientation of education from character formation toward the attainment of instrumental competencies. This condition underscores the need to reconstruct the Islamic educational paradigm by positioning ethics and the concept of the soul as foundations for the formation of holistic human beings. This study aims to analyze the reconstruction of human identity through the integration of Islamic ethics and the concept of the soul from the perspective of Islamic education. The study employed a qualitative approach using a library research method through a review of classical and contemporary literature on the concepts of the soul (nafs), intellect (‘aql), heart (qalb), spirit (rūḥ), and Islamic ethics in education. The data were analyzed using content analysis and a hermeneutic approach to identify the conceptual interrelationships among these components. The findings indicate that human identity in Islamic education is formed through the integration of spiritual, intellectual, moral, and social dimensions centered on the purification of the soul (tazkiyat al-nafs), the formation of moral character, the development of transcendental awareness, and the strengthening of individual and social responsibility. Islamic ethics serves as a normative guide, whereas the concept of the soul provides an ontological foundation for the formation of a human personality oriented toward a balance between worldly life and the afterlife. This study concludes that the reconstruction of human identity requires an Islamic educational paradigm that integrates ethical, spiritual, and intellectual dimensions into a unified systemic framework. These findings provide a conceptual foundation for the development of curricula, learning strategies, and Islamic education policies oriented toward holistic character formation and the strengthening of human identity amid the dynamics of global civilization.